A Three‐Locus, PCR‐based Method for Forensic Identification of Plant Material1. Issue 4 (1st December 2017) - Srivastava, Tushar; Wu, Michael; Kakhnovich, Julia; Waithaka, Bridgit; Lents, Nathan H.
Abstract: Plant residue is currently an underutilized resource in forensic investigations despite the fact that many crime scenes, as well as suspects and victims, harbor plant‐derived residue that could be recovered and analyzed. Notwithstanding the considerable skill of forensic botanists, current methods of species determination could benefit from tools for DNA‐based species identification. However, DNA barcoding in plants has been hampered by sequence complications in the plant genome. Following a database search for usable barcodes, broad‐spectrum primers were designed and utilized to amplify and sequence the rbcL, trnL‐F, and rrn18 genetic loci from a variety of household plants. Once obtained, these DNA sequences were used to design species‐targeted primers that could successfully discriminate the source of plant residue from among the 21 species tested.